Middle Aortic Syndrome in a Child-Bearing Age Patient - Rabenstein, Andrew P.; Salhab, Khaled F.; Spentzouris, Georgios; Paruchuri, Vijayapraveena; Hines, George; Vintzileos, Anthony M.; Schubach, Scott L. (AORTA, 2019)
We report a rare case of a 30-year-old female who had a long-standing history of middle aortic syndrome that was being managed nonsurgically. She presented with hypertension and buttock pain with plans to become pregnant. She underwent an aortoiliac bypass.
Keywords: aorta; thoracoabdominal aorta; pregnancy